PERILAKU SELF-HARM ATAU MELUKAI DIRI SENDIRI YANG DILAKUKAN OLEH REMAJA (SELF-HARM OR SELF-INJURING BEHAVIOR BY ADOLESCENTS) - Thesalonika Tarigan; Nurliana Cipta Apsari (Universitas Padjadjaran, 2021)
Self-harm behavior is a form of behavior that done to deal with emotional distress or emotional pain by hurting him/herself without any intention of committing suicide. From various studies, adolescents are the one who have high intention of this behavior. There is still a few research for this issue because of the iceberg phenomenon. This issue rated as iceberg phenomenon because there is much number of cases that have not been revealed. This article provides a literature review on self-harm or self-injuring behavior in adolescents and the factors that have the potential to cause self-injury in adolescents. The research objective was to find out and get more information about self-harm behavior. The method that was used in this article is a literature review. The result is self-harm behavior mostly done by adolescent because adolescence is a period of time where there are full of conflicts so that they are vulnerable to doing self-harm. Potential factors to cause adolescents to injuring themself which was discussed below are loneliness, high level of difficulty in responding to negative experiences and a low level of tolerance for the problem sat hand, emotional focus coping, external and internal factors, and communication patterns/style with parents.